Effects of Small-Scale Gold Mining (SGM) to Mercury and Nutrient Contents in Soil in Kokap Subdistrict, Kulonprogo, Yogyakarta - Ernawati, Rika; Cahyadi, Tedy Agung; Rambe, Shahensahb Anand Anggian (RSF Conference Series: Engineering and Technology, 2022)
Gold processing in Dusun Sangon, Kalirejo Village, Kokap Sub district, Kulonprogo Regency, Special Region of Yogyakarta Province uses amalgamation method. Mercury use in gold processing has a potential impact on environmental damage and health of organism. Therefore, management on mercury-contaminated soil is needed to reduce environmental impacts. However, before performing soil management, it is important to conduct research on initial condition of research location, including research on the soil’s nutrient quality and mercury content. Testing was conducted in the laboratory. Mercury (Hg) content testing used mercury analyzer testing method. pH testing used ISRIC 6th 2002 method. Organic carbon testing used SNI 13-4720-1998 testing method. Total nitrogen testing used SNI 2803-2010 testing method. C/N Ratio testing used SNI 13-4720-1998; SNI 2803-2010 testing methods. Results show that mercury contents in residual samples of gold ore and soil samples were 4.81 mg/kg and 88.63 mg/kg respectively, which were included in TC-B and TC-A in the aforementioned order. Meanwhile, mercury content in gold ore Samples 1 and 2 were 0.28 ppm and 0.14181 ppm respectively. Soil nutrient content parameters of Organic C, Total N, and C/N ratio were found to be very low. These results might be influenced by processing activities in gold ore mining.